INOVASI, INVESTASI, DAN PERTUMBUHAN EKONOMI BERBASIS ISLAM - Noni Zahriya Tanjung; Zainal Efendi Hasibuan (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
This study aims to examine the relationship between innovation, investment, and Islamic-based economic growth. The Islamic economic approach provides the foundation for an economic system that focuses on justice, ethics and Islamic values. Innovation and investment are considered as important factors driving sustainable economic growth in the context of an Islamic-based economy. In the context of technological innovation, it includes the development and application of technology that is in accordance with sharia principles, such as environmentally friendly technology and technology that supports halal economic activities. Islamic-based investment involves sharia-compliant principles and financial instruments that cover investment. Islamic-based economic growth refers to economic growth that occurs in compliance with sharia principles, such as being fair, transparent and sustainable. This study analyzes the relationship between innovation, Islamic-based investment, and economic growth using empirical data and quantitative analysis. The results of this study are expected to provide insight into the importance of innovation and investment in accelerating sustainable economic growth in the context of an Islamic-based economy.